How to cheat in Photoshop Elements 12 : release your imagination - Asch, David (How to cheat in Photoshop, 2014)
"Have you ever wanted to summon magical powers? Appear in a graphic novel? Or control the weather and seasons? There's a whole world of opportunity out there for creating fun photomontages, powerful panoramas, and dynamic distortions. How to Cheat in Photoshop Elements 12 starts you at the basics of photomontage with selection techniques, layers and transformations; leading up to full-length projects for creating magazine covers, fantasy scenes, poster artwork and much, much more. This book also features: - A dedicated website where you can download images and tutorial videos that show you how to expand, develop, and master top techniques. - Full color images, a glossary of terms, useful keyboard shortcuts, and a detailed index that will help you locate that fantastic technique in a flash. "We recommend this book for all Elements users aiming to push boundaries." Photoshop Creative "It's a photo manipulator's dream book, and tops for any Photoshop library." Midwest Book Review "The perfect book for you." What Digital Camera "We think Adobe should include this book with every copy of Adobe Photoshop Elements." PC Advisor "No boring background, just all the answers!" RetouchPRO"--